FACTORS AFFECTING THE STOCK PRICES OF MANUFACTURING COMPANIES LISTED ON THE LQ45 INDEX OF THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2019 – 2023 - Salim, Steven Jonathan; Tannia, Tannia (Graduate Program of Universitas Tarumanagara, 2025)
Thistresearchtaimsttotprovidetempiricaltevidencetregarding the impact of debtttotequity ratiot (DER), net profittmargint (NPM), returntontassets (ROA), returntontequity (ROE), current ratio (CR), andtprice earning ratio (PER) variables on the stocktprices of manufacturing companiestlisted on the LQ45 index in the IndonesiatStock Exchangetfor the period of 2019-2023. This researchtuses secondary data with a quantitative approach and Purposive Sampling applied as the sampling method. Thetsample usedtintthis research are 14 manufacturing companiestin the LQ45 index category of the Indonesian StocktExchange (IDX) in thet2019-2023 period. This research has been tested with the SPSS 27 statistical testing tool totprove thethypothesis proposal. The resultstof the analysistshow thattthe researchtvariable simultaneously has atsignificant effectton stock prices and the partialttest results show that the Debttto EquitytRatio, NettProfittMargin, Return ontAssets, Return ontEquity, and the Current Ratio have a significant effectton stock prices. Meanwhile the Price Earning Ratio has notsignificant effectton stock pricestin manufacturing companiestin the LQ45 Index category of the Indonesiantstock exchangetfor the period 2019 - 2023.